Prediction Equations for Salinity Appraisal in Clay Loam Soils of Southern Iraq - Aggarwal, R K; Hussain, Tahir; El-Dosoky, H (Annals of Arid Zone, 2016)
soil: water extracts (1 : 2, 1 : 3, I : 4 and 1 : 5) in clay loam soils of southern Iraq. The results indicated a significant linear relationship with measured and calculated values from the regression equations developed from the above soil: water extracts. Out of the different soil: water extracts, the prediction equation from 1 : 3 soil water extract showed the highest predictability (99.4%) with least standard deviation of difference. This equation when tested for ECe of samples from Missan province, confirmed its suitability. The regression equation was as follows: Y=0.5+3.51 X (r=0.997**) where, Y=ECe; and X =EC in 1 : 3 soil water extract.